Corporate Social Responsibility: Environmental Concern Through the Application of Communitarian Citizenship Thinking - Fahmi, Rizal; Hilal Ramdhani; Hudaya Latuconsina; Sri Jaya Lesmana (Universitas Negeri Semarang, 2024)
Environmental awareness is an integral part of the sustainability of ecosystems worldwide that are starting to be damaged due to rapid industry. The rise of industrial companies in Indonesia impacts environmental damage and has drawn criticism from the community, so corporate social responsibility was formed, which is a form of corporate commitment to its social environment to maintain environmental sustainability and empowerment of the surrounding community. Ideologically, environmental damage is inseparable from the muscular liberalism that pays little attention to ecological elements. This paper seeks to raise an alternative study of communitarian CSR that understands environmental awareness. Communitarianism focuses on the social reality that must be maintained and cared for to raise collective consciousness, including environmental elements. This paper uses a literature study to examine the understanding of communitarianism. The knowledge gained from the literature search is that communitarianism provides a different perspective from liberalism regarding self and environment, so it is interesting to apply communitarian thinking in companies to implement environmental awareness as an alternative to solving environmental problems where this condition indicates the need for a movement based on communal awareness in reforestation. The more communal awareness of nature is built on the impact of community pressure on the government to make a rule that pays attention to environmental problems.